Faktor-Faktor Yang Mempengaruhi Pengeluaran Pangan Rumah Tangga Petani Cengkeh di Desa Totallang Kecamatan Lasusua Kabupaten Kolaka Utara - Sahudini, Mega Silvia; Yunus, Lukman; Zani, Munirwan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This research was motivated by Totallang Village, one of the plantation commodity-producing villages in North Kolaka Regency. Based on the results of the initial survey, it was found that in Totallang Village there were 187 households or all households that sought clove farming as a source of household income. Thus, farmer households do not produce their own staple food for household consumption, so they must buy to meet food needs. The aim of the study was to find out and analyze the amount of food expenditure for clove farmer households in Totallang Village and the factors that influence the food expenditure of clove farmers in Totallang Village. Location determination is determined intentionally (purposive). The number of respondents is 65 people. Quantitative descriptive analysis is used to calculate and describe the allocation of household food expenditure and multiple non-linear regression analysis is used to analyze the factors that influence household food expenditure. Data analysis using formulas Y = a + b1x1 + b2x2 + b3x3 + b4x4 + e. The results showed that the average food expenditure of respondents was Rp. 13,722,553 /farmer household /year and household income factors and the number of family members partially have a significant/significant effect on food expenditure. While the education of the head of the household and the education of housewives did not significantly influence food expenditure.